Is Allelopathic Activity of Ipomoea murucoides Induced by Xylophage Damage? - Alejandro Flores-Palacios; Angélica María Corona-López; María Yolanda Rios; Berenice Aguilar-Guadarrama; Víctor Hugo Toledo-Hernández; Verónica Rodríguez-López; Verónica Rodríguez-López; Susana Valencia-Díaz (PLoS ONE, 2015)
Herbivory activates the synthesis of allelochemicals that can mediate plant-plant interactions. There is an inverse relationship between the activity of xylophages and the abundance of epiphytes on Ipomoea murucoides. Xylophagy may modify the branch chemical constitution, which also affects the liberation of allelochemicals with defense and allelopathic properties. We evaluated the bark chemical content and the effect of extracts from branches subjected to treatments of exclusion, mechanical damage and the presence/absence of epiphytes, on the seed germination of the epiphyte Tillandsia recurvata. Principal component analysis showed that branches without any treatment separate from branches subjected to treatments; damaged and excluded branches had similar chemical content but we found no evidence to relate intentional damage with allelopathy; however 1-hexadecanol, a defense volatile compound correlated positively with principal component (PC) 1. The chemical constitution of branches subject to exclusion plus damage or plus epiphytes was similar among them. PC2 indicated that palmitic acid (allelopathic compound) and squalene, a triterpene that attracts herbivore enemies, correlated positively with the inhibition of seed germination of T. recurvata. Inhibition of seed germination of T. recurvata was mainly correlated with the increment of palmitic acid and this compound reached higher concentrations in excluded branches treatments. Then, it is likely that the allelopathic response of I. murucoides would increase to the damage (shade, load) that may be caused by a high load of epiphytes than to damage caused by the xylophages.